HOLOCENE DEFORMATION IN THE WESTERN END OF THE TUNKA SYSTEM OF RIFT BASINS - Arzhannikova A.V.; Larroque C.; Arzhannikov S.G. (My University, 2003)
We investigate the geometry and kinematics of Holocene active compressional structures in the Mondy basin and its surroundings (western termination of the Tunka system of rift basins) and continue the discussion on the M - 7 Mondy earthquake of 4 April 1950. The Holocene reverse-oblique motions along the W-E trending Mondy and Ikh-Uhgon faults are interpreted in the context'of Late Cenozoic evolution of a flower structure, on the basis of deciphered digital SPOT (10 m resolution) and Landsat (30 m resolution) imagery and field geomorphological measurements.
Keywords: Tectonic deformation; fault kinematics; earthquake; strain field; Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен